Engineering bunched RhTe nanochains for efficient methanol oxidation electrocatalysis. Issue 88 (15th October 2020) - Wang, Ziqiang; Zhang, Hugang; Liu, Songliang; Dai, Zechuan; Wang, Peng; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : We report a two-step method for the synthesis of bunched RhTe nanochains for excellent electro-oxidation of methanol. Abstract : Herein, a two-step method is proposed to synthesize bunched RhTe nanochains (RhTe NCs) using Te nanowires and formic acid both as a reductant and a structure-directing agent. The resultant RhTe NCs possess a high electrochemical active surface area of 89.3 m 2 gRh −1, and exhibit superior catalytic activity and durability towards the electro-oxidation of methanol in an alkaline medium.